INTERVENSI MILITER RUSIA TERHADAP REPUBLIK OTONOMI KRIMEA, UKRAINA PERIODE 2013-2022 SEBAGAI PELANGGARAN HUKUM INTERNASIONAL - Septian Wahyudi (Journal of International Relations, 2022)
Russian military attack upon Ukraine on February 2022 spark and old conflict that started on the same month in 2014. Russian military intervention in 2014 against Ukraine’s territory culminating in Crimea’s annexation started the worsening relation between the two nations. Upon the aftermath of the annexation, question on the legitimacy of both the intervention and the annexation rises. Meanwhile Russian keep claiming the annexation is legitimate, several United Nations, including Ukraine, disapproved and refused the annexation of Crimea by Russia. The research was made through the collection of qualitative data, as well as the concept of military intervention and crime of aggression. This research analyzes on how the Russian military intervention against the Autonomous Republic of Crimea, Ukraine during 2013-2022 period is categorized as international law violation. The result of this study explains that aforementioned military intervention wasn’t legitimate based on faulties in the justification used by the Russian. The justification including invitation, self-defense, and the Crimean parliament’s referendum on the annexation. The results furthermore explains that according to UN Resolution 3314, this military intervention is a crime of aggression.Keyword: Russia, Ukraine, Crimea, Military Intervention, Violation of International Law, Crime of Aggression